Synthesis of novel alpha-aminophosphonate derivatives, biological evaluation as potent antiproliferative agents and molecular docking - Deshmukh, Satish U. (ChemistrySelect, 2018)
A series of novel fluorine containing α‐aminophosphonate derivatives (4 a–4 q) were synthesized in excellent yield and high purity. All these novel Fluorinated α‐aminophosphonate compounds were screened for antiproliferative and apoptosis activity on human non small cell lung carcinoma cells (A549) and human skin melanoma cells (SK‐MEL‐2). Compounds 4 a, 4 b, 4 c, 4 f, 4 i, 4 j and 4 m were found to be more active antiproliferative agent against A549 and SK‐MEL‐2 cells with IC50 value 0.22 to 1.25 μM. Molecular docking study related to binding affinity and binding mode analysis showed that synthesized compounds had potential to inhibit human Topoisomerase IIa enzyme system. Flow cytometric study showed some of these derivatives also induced cell apoptosis and arrest cell cycle at G1 and at G2/M phase. Overall, this study provides future perspective of lead candidate for the future anticancer drug discovery initiatives.

Ultrasound assisted synthesis of 4-(Benzyloxy)-N-(3-chloro-2-(substitutedphenyl)-4-oxoazetidin-1-yl) benzamide as challenging anti-tubercular scaffold - Nimbalkar, Urja D.; Seijas, Julio A.; Borkute, Rachna; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Sarkar, Dhiman; Nikalje, Anna Pratima G. (Molecules, 2018)
A series of ten novel derivatives of 4-(benzyloxy)-N-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl) benzamide 6a-j were synthesized in good yield from the key compound 4-(benzyloxy)-N-(substituted benzylidene) benzo hydrazide, called Schiff `s bases 5a-j, by Staudinger reaction ([2 + 2] ketene-imine cycloaddition reaction) with chloro acetyl chloride in the presence of catalyst tri ethylamine and solvent dimethyl formamide (DMF), by using ultra-sonication as one of the green chemistry tools. All the synthesised compounds were evaluated for in vitro anti-tubercular activity against Mycobacterium tuberculosis (MTB) and most of them showed promising activity with an IC50 value of less than 1 mu g/mL. To establish the safety, all the synthesized compounds were further tested for cytotoxicity against the human cancer cell line HeLa and all 6a-j compounds were found to be non-cytotoxic in nature. The molecular docking study was carried out with essential enzyme InhA (FabI/ENR) of Mycobacterium responsible for cell wall synthesis which suggests that 6a and 6e are the most active derivatives of the series. The theoretical evaluation of cell permeability based on Lipinski's rule of five has helped to rationalize the biological results and hence the synthesized azetidinone derivatives 6a-j were also analyzed for physicochemical evaluation that is, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties and the results showed that all the derivatives could comply with essential features required for a potential lead in the anti-tubercular drug discovery process.
Keywords: ADMET study; anti-tubercular screening; azetidinone; cytotoxicity study; green chemistry; Molecular docking; ultra-sonication